Strengthening storage, credit, and food security linkages: The role and potential impact of warehouse receipt systems in Malawi - Edelman, Brent; Lee, Hak Lim; Mabiso, Athur; Pauw, Karl (International Food Policy Research Institute, 2015)
This study considers the extent to which smallholder farmers, including those who do not necessarily produce a surplus for the market, might benefit from participating in warehouse receipt systems (WRS) in terms of improved income and food security. We consider three potential channels: efficient food markets; reduced post-harvest losses; and access to credit. Firstly, we find that WRS, through its potential to increase demand for storage and facilitate temporal arbitrage, could address high price seasonality driven by high transport margins and thin commodity markets. By lowering price seasonality, WRS would benefit net-consuming households that tend to sell low and buy high. However, since temporal arbitrage transactions are associated with costs and price risks, engaging in them becomes undesirable if prices do not follow predictable seasonal patterns. Prices tend to be less predictable in countries such as Malawi where government market intervention is highly discretionary.